Successful Transplantation of Frozen-thawed Calf Spermatogonial Stem Cells to the Mouse Testis - Peyman Rahimi-Feyli; Parviz Tajik; Morteza Koruji; Shiva Shafiei; Maria Zahiri (مجله دانشکده پزشکی اصفهان, 2013)
Background: Spermatogonial stem cells (SSCs), the only adult stem cells capable of transferring genetic information to the next generation, are important in cell biology. The most important applications of these cells include the treatment of infertility, fertility preservation of oncological patients, and the creation of transgenic animals. The aim of this study was to evaluate the possibility of transplantation of frozen-thawed bovine spermatogonial cells to the testis of an azoospermic mouse model and to prove the presence of spermatogonial stem cells among bovine spermatogonial cells isolated and proliferated by methods used in the study. Methods: Spermatogonial cells were isolated from 3 to 5 month-old bull calves and then were frozen-thawed. Subsequently, the cells were cultured in the presence of glial cell line-derived neurotrophic factor (GDNF 40 ng/ml) for 2 weeks. The stemness of these cells was evaluated by transplanting them to the testis of azoospermic mouse models. Findings: The viability rate of fresh cells and frozen cells after thawing were 87.4 ± 2.4 and 65 ± 1.7, respectively, that corresponds to a significant difference (P < 0.01). After one month, the mice were euthanized and the histopathological evaluation of their testes with fluorescent microscope showed the colonization of marked bovine SSCs in the mouse seminiferous tubules. Conclusion: In our knowledge, this is the first reported case of xenotransplantation in Iran. The results of this study showed that the xenogeneic transplantation of calf frozen-thawed spermatogonial cells to the mouse testis has been successful and SSCs were present among the transplanted cells. Keywords: Spermatogonia, Stem cell transplantation, Testis, Animal models